Yield equation and biomass expansion factor for above ground carbon density estimation of smallholder tree plantations in Northern Mindanao - Palma, Richmund A. (2011)
Regression equations for the estimation of tree volume and biomass expansion factor (BEF) in a smallholder A. mangium plantation were developed based on direct measurements of trees in Northern Mindanao, Philippines. A. mangium is an important smallholder tree plantation species and commodity for wood industry in the region and the country. Sound and effective management of smallholder tree plantation for wood production and carbon sequestration necessitates information on yield. The study was designed to develop reliable yield prediction equation and BEF according to various ages, site qualities and spacing. Fifty temporary sample plots were established in Claveria, Misamis Oriental with a total of 3,910 trees measured. The study had generated two equations: 1)yield prediction equation (lnYIELD = -4.250101 + 2.017218*lnAGE + 1.079861*lnSI + .2352149*lnSP); and 2) BEF (BEF = 1.693517*0.9938733^VB). The yield prediction equation can be employed as a basis for efficient management and development of smallholder tree plantations. The tre farmers could make use of the yield tables in determining the volume of wood that can be harvested, economic rotation, cut schedule, plantation development schedule and business projection. The yield equation and BEF can also be used to predict above ground biomass carbon density for smallholder A. mangium plantation. The equations have been developed for plantations located in Claveria, Misamis Oriental particularly those with ages ranging from 3 to 18 years old, site index ranges from 12 to 25 meters, and spacing of 2m x 2m, 1m x 4m, 2m x 3m, 1m x 6m, 2m x 4m, 3m x 3m, 3m x 4m, 2m x 6m, and 1m x 8m. the equations were applicable outside the study area but careful validation should be done to ensure effective A. mangium tree plantation establishment and management.
Keywords: Biomass; Tree farm industry; Mindanao